2021
DOI: 10.21608/tsnj.2021.208735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Guidelines on Nurses' Knowledge and Practice Regarding Central Line Associated Blood Stream Infection at Intensive Care Unit

Abstract: Background: Central line associated blood stream infections are serious but can often be prevented when evidence-based guidelines that are used by critical care nurse through utilized infection control measures during insertion and maintenance of central lines. Aim of the study was to evaluate the effect of educational guidelines on nurse's knowledge and practice regarding central line associated blood stream infection at intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…Regarding their educational level, about half of the nurses under study had bachelor's degree. This finding was in the same line with Zeyada et al, (2021) showed that nurses' knowledge levels were extremely low before being exposed to a defined training program, which enhanced significantly and rapidly after application but then slightly declined at follow-up. Additionally, this outcome was consistent with El-Sol and Badawy's (2020), in their study on the impact of a planned teaching module on ICU nurses' knowledge and practice regarding prevention of central line associated bloodstream infection occurs with total parenteral nutrition, they discovered that nurses' knowledge had significantly improved following the planned teaching module.…”
Section: The Second Sessionsupporting
confidence: 87%
“…Regarding their educational level, about half of the nurses under study had bachelor's degree. This finding was in the same line with Zeyada et al, (2021) showed that nurses' knowledge levels were extremely low before being exposed to a defined training program, which enhanced significantly and rapidly after application but then slightly declined at follow-up. Additionally, this outcome was consistent with El-Sol and Badawy's (2020), in their study on the impact of a planned teaching module on ICU nurses' knowledge and practice regarding prevention of central line associated bloodstream infection occurs with total parenteral nutrition, they discovered that nurses' knowledge had significantly improved following the planned teaching module.…”
Section: The Second Sessionsupporting
confidence: 87%
“…Patient safety can be little addressed in professional training and, when addressed, this is done only occasionally, with no in-depth reflections. Therefore, improvement in the training and qualification processes, regarding aspects related to CVC-associated PBSI, with a view to improving the quality of care, is required for professionals already in the job market (13) .…”
Section: Discussionmentioning
confidence: 99%
“…A segurança do paciente pode ser pouco abordada na formação profissional e, quando abordada, é de maneira pontual sem reflexões aprofundadas. Portanto, são necessárias melhorias no processo formativo e capacitações aos profissionais já inseridos no mercado de trabalho no que tange a aspectos relacionados às IPCS associadas a CVC, com vistas a melhoria da qualidade da assistência (13) .…”
Section: Discussionunclassified